Implications of flow regulation for habitat conditions and phytoplankton populations of the Nakdong River, South Korea. (1st December 2021) - Kim, Hyo Gyeom; Recknagel, Friedrich; Kim, Hyun-Woo; Joo, Gea-Jae
Highlights: Changes in mechanisms of phytoplankton dynamics with flow regulation were assessed. Effects of hydrological variables were weakened in the post-regulation period. Phytoplankton phenology altered owing to altered nutrient & zooplankton relations. Flow regulation altered habitat conditions of rivers to those of stagnant waters. Abstract: Anthropogenic regulation of hydrographs is a widespread approach to river management; however, the effects of river regulation on habitat conditions and aquatic communities have rarely been studied. In this study, we analyzed the physical, chemical, and biological data from the lower Nakdong River in South Korea from 2005 to 2009 before weir construction and from 2012 to 2016 after weir construction. A partial least square path model (PLS-PM) was applied to delineate the complex interrelationships of diatoms and cyanobacteria with physicochemical parameters, nutrients, zooplankton grazing, and hydrological parameters. Inferential modeling using the hybrid evolutionary algorithm (HEA) allowed the identification of differences in the importance and threshold conditions of population dynamics drivers of diatoms and cyanobacteria before and after flow regulation. The annually averaged trajectories of limnological variables displayed significant shifts in seasonality and magnitudes of phytoplankton, zooplankton, and nutrient concentrations between the two periods. The results of PLS-PM indicated that, after flow regulation, diatoms and cyanobacteria were directly affected by nutrients and zooplankton densities and the path coefficients of hydrological parameters decreased or even were insignificant. The inferential models suggested that diatom dynamics were essentially shaped by threshold conditions of water temperature (WT) and pH before regulation, but mainly by those of rotifers (below 51.1 ind. L −1 ) after regulation. As for cyanobacteria dynamics, WT was identified as a critical threshold condition before and after regulation, and the threshold of PO4 − concentration above 145.4 L −1 was identified as the reason for occasional blooms during the post-regulation period. Overall, the results suggest that flow regulation gradually alters habitat conditions typically of rivers to those of stagnant waters. These findings must be taken into account for sustainable management strategies of regulated rivers.